The effect of local labour market conditions on the decision to migrate among UK graduates - Rick Audas; Peter Dolton (European Regional Science Association (ERSA), 1998)
Using Higher Education Statistics Agency (HESA) "first destinations " data we model two key aspects of individual?s higher education experience. First, we explore where UK university entrants choose to study and what factors influence the decision to migrate to another region to study. We are particularly interested in looking at how socio-economic background influences institutional choice for North East residents. The HESA data includes postcode information for the individual?s residence immediately prior to entering HE. Having full postcodes enables us to "super-profile" the individuals, which allows us to make inferences about their backgrounds, including the conditions in their local labour market. Second, we explore the subsequent post-graduation transition into work, looking at how regional mobility influences occupational outcomes. In particular, we are interested in determining the extent to which the "best" graduates are geographically mobile. The inclusion of full postcode data in the HESA data also allows us to look at the exogonous effects of local unemployment rates in the location where the individual studied and also in the location where the individual resides, to determine how this effects the migration decision. Econometric modelling in this context uses the "Mover-Stayer" model with our exogonous data aiding formal identification via exclusion restrictions. After modelling the migration decision, we estimate the economic returns to migration. Using longitundinal data on a sample of approximately 15,000 UK graduates from 1985 and 1990, we estimate earnings equations with the inclusion of a range of mobility questions included as regressors. In particular, we are interested in determining the importance of an early move on one?s future earnings. These are particularly important questions for the UK, where graduate opportunities differ considerably from region to region. One of the principal benefits of increased participation in higher education is a more skilled labour market. However, the distribution of these skills is not equal across regions and one of the principal reasons for this is a lack of opportunity to put these skills to use. Furthermore, our results will have increasing relevance to the higher education system as a whole since it is anticipated that changes in the fees system will cause a large increase in the propensity to go to one?s local university.
Keywords: 330